Development of learning cycle box media for children in Wiropati Hamlet, Magelang - Rochiyati Murniningsih; Ashadi Sulthon; Zaki Zaki; Titania Ayu Rizqia; Faza Khusu Sa’adah; Ega Aldanisa Apriliani (Universitas Muhammadiyah Magelang, 2023)
The development of the learning cycle box media is a dissemination of science and technology for the Wiropati hamlet community who are experiencing problems in the learning process at home due to the Covid-19 pandemic. Learning cycle box media development activities are made to increase the attractiveness of school-age children to return to learning. This activity is in the form of mentoring learning cycle box media for elementary age children in collaboration with Sahabat Rumah Baca. The method is carried out through production practices and mentoring in the application of the learning cycle box. The results achieved were an increase in the learning motivation of the school-age children, as evidenced by the enthusiasm of attendance during learning activities.